2021
DOI: 10.3389/fmed.2021.645975
|View full text |Cite
|
Sign up to set email alerts
|

Is Perioperative Dexmedetomidine Associated With a Reduced Risk of Perioperative Neurocognitive Disorders Following Cardiac Surgery? A Systematic Review and Meta-Analysis With Trial Sequential Analysis of Randomized Controlled Trials

Abstract: Background: To assess the effect of dexmedetomidine on the reducing risk of perioperative neurocognitive disorders (PNDs) following cardiac surgery.Methods: A systematic review and meta-analysis with trial sequential analysis (TSA) of randomized controlled trials were performed. PubMed, Embase, Cochrane Library, and CNKI databases (to August 16, 2020) were searched for relevant articles to analyze the incidence of PND for intraoperative or postoperative dexmedetomidine administration after cardiac surgery. PND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 53 publications
(137 reference statements)
4
16
0
Order By: Relevance
“…17 and Xiong et al had opposite findings and the result of pooled studies was found to be in favor of dexmedetomidine in reducing POD in cardiac surgery patients. 18,19 Thus the literature is largely conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…17 and Xiong et al had opposite findings and the result of pooled studies was found to be in favor of dexmedetomidine in reducing POD in cardiac surgery patients. 18,19 Thus the literature is largely conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these results suggest that dexmedetomidine may reduce the extent of brain insult following cardiac surgery. Xiong et al ( 188 ) conducted a systematic review on the effects of dexmedetomidine on perioperative neurocognitive disorders. With data from 3610 patients collated from 24 studies, they detected no significant difference in the incidence of POCD between dexmedetomidine and the control group (OR: 0.47, 95% CI: 0.22–1.03, p = 0.060).…”
Section: Pathophysiology Of Postoperative Cognitive Dysfunction Follo...mentioning
confidence: 99%
“…It should be noted that numerous studies may have used an insufficient maintenance dose of dexmedetomidine, ranging between 0.2–0.5 ug/kg/hr of dexmedetomidine. In contrast, there was a significant reduction in the incidence of postoperative delirium in the dexmedetomidine group compared to the control group (OR: 0.59, 95% CI: 0.43–0.82, p = 0.001) ( 188 ).…”
Section: Pathophysiology Of Postoperative Cognitive Dysfunction Follo...mentioning
confidence: 99%
“…We checked the eligibility of all studies from previous meta-analyses and updated literature search according to the following criteria [12][13][14][15] : (1) adult patients were assigned to receive cardiac surgery, regardless of types of surgeries;…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…However, the optimal time of applying dexmedetomidine to prevent the occurrence of POD in patients undergoing cardiac surgery was still not investigated in these meta-analyses. 14,15 Unfortunately, to our knowledge, there was no study directly compared the different administration time of dexmedetomidine. Therefore, it is impossible to determine the optimal administration time of dexmedetomidine in patients undergoing cardiac surgery from pairwise meta-analysis.…”
Section: Introductionmentioning
confidence: 99%